Modeling of the Extraction Kinetics of Oil from Safou Pulp (Dacryodes edulis H.J. Lam) by Heating in Hexane with Stirring - Bopoundza, Feueltgaldah-Christian; Binaki, Anicet Fréderic; Biassala , Eliane Thérèse; Loumouamou , Bob Wilfrid; Ngueko, Séraphin Nguié; Massamba, Julin Aaron Siassia; Silou, Thomas (International Journal of Applied Sciences and Biotechnology, 2024)
The continuous extraction of oil from safou pulp in hot hexane with stirring was studied. Two factors were considered: the method with two modes, M1 and M2, respectively without and with prior preheating of the solvent, and the temperature with two modes as well, 90 and 105°C for M1, and 50 and 70°C for M2. The results showed that continuous extraction by direct contact of the substrate with the solvent yields lower results compared to Soxhlet extraction, which has the advantage of regenerating the pure solvent each time, leading to more efficient recovery of the solute. However, the extraction rate is proportional to the preheating of the solvent, temperature, and agitation of the system, compared to previous results. The extraction curves exhibit the usual pattern of solid-liquid extraction of plants, with an ascending phase followed by stabilization. The temperature stabilization phase was not observed. The experimental curves validate the Peleg model, but not the first-order kinetic model. The oil is extracted by elution and diffusion. Peleg's lines, t/Yt = 0.01855t + 0.13074 at 90 °C and t/Yt = 0.02076t + 0.05839 at 105 °C for method M1, and t/Yt = 0.01842t + 0.03657 at 50 °C and t/Yt = 0.01934t + 0.02647 at 70 °C for method M2, characterizing the extraction process, confirm the previous conclusions. The initial extraction rates, respectively equal to 7.65, 17.13, 27.34, and 37.77 %.min-¹, are proportional to the extraction temperature and higher when the solvent is preheated. The activation energy values, 61.31 kJ.mol-¹ for method M1 and 14.88 kJ/mol for method M2, clearly show the benefit of preheating the solvent before starting the extraction. Int. J. Appl. Sci. Biotechnol. Vol 12(4): 224-234.